ATM rs189037 significantly increases the risk of cancer in non-smokers rather than smokers: an updated meta-analysis. Issue 6 (28th June 2019) - He, Xiaoxia; Wang, Peng; Li, Ying; Shen, Na
Abstract : Rs189037 (G>A) is an important functional variant with ataxia telangiectasia mutated ( ATM ) gene, which might affect ATM 's expression involvement in several human cancers. Increasing evidence reveals that smoking-related cancers have distinct molecular characteristics from non-smoking cancers. Until now, the role of ATM rs189037 in cancer risk stratified by smoking status still remains unclear. To evaluate the association between ATM rs189037 and cancer risk based on smoking status, we performed this meta-analysis by a comprehensive literature search via databases of PubMed, Embase, Web of Science and CNKI, updated till January 2019. Multivariate-adjusted odds ratios (ORs) and 95% confidence intervals (CIs) were extracted from eligible studies if available, to assess the relationship strengths. A total of seven eligible studies were included, comprising 4294 cancer patients (smokers: 1744 [40.6%]) and 4259 controls (smokers: 1418 [33.3%]). Results indicated a significant association of ATM rs189037 with cancer risk. In non-smokers, compared with GG genotype, AA genotype increased a 1.40-fold risk of overall cancer (OR = 1.40, 95% CI = 1.15–1.70, P heterogeneity =0.433, I 2 = 0.0%). Subgroup analysis in lung cancer (LC) also exhibited a significant result (OR = 1.41, 95% CI = 1.15–1.73, P heterogeneity =0.306, I 2 = 17.0%) only in non-smokers. However, the association was not observed in smokers, no matter for overall cancer or for LC. Our findings highlight that ATM rs189037 significantly increases cancer susceptibility in non-smokers, rather than in smokers. The association is prominent in LC.